2017
DOI: 10.1093/mnras/stx559
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the extremely fast disc wind in a gravitationally lensed quasar APM 08279+5255

Abstract: The gravitationally lensed quasar APM 08279+5255 has the fastest claimed wind from any AGN, with velocities of 0.6-0.7c, requiring magnetic acceleration as special relativisitic effects limit all radiatively driven winds to v<0.3-0.5c. However, this extreme velocity derives from interpreting both the narrow and broad absorption features in the X-ray spectrum as iron absorption lines. The classic ultrafast outflow source PDS 456 also shows similar absorption systems, but here the higher energy, broader feature … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 69 publications
2
28
0
Order By: Relevance
“…Such an intermediate magnification factor is also in agreement with the upper limit of µ 8.2 derived by Saturni et al (2016) from the RM. We also note that a lower limit on APM 08279+5255 black hole mass M BH 4 × 10 9 M has been derived by Hagino et al (2017) through SED modeling. Using our fiducial luminosity and FWHM measurements for Mg II in Eq.…”
Section: Single-epoch Black Hole Mass Estimatesmentioning
confidence: 80%
See 1 more Smart Citation
“…Such an intermediate magnification factor is also in agreement with the upper limit of µ 8.2 derived by Saturni et al (2016) from the RM. We also note that a lower limit on APM 08279+5255 black hole mass M BH 4 × 10 9 M has been derived by Hagino et al (2017) through SED modeling. Using our fiducial luminosity and FWHM measurements for Mg II in Eq.…”
Section: Single-epoch Black Hole Mass Estimatesmentioning
confidence: 80%
“…Serendipitously discovered in a Galactic survey for cold carbon stars (Irwin et al 1998), it is archetypal to several categories of the quasar class, showing together many of the observational phenomena that can be found in such objects. In fact, beyond having evidence of both broad and intrinsic narrow (Ellison et al 2004) absorption features associated with the C IV λ1549 emission line, it also shows an uncommon O VI λ1030 BAL embedded in the Lyα forest (Hines et al 1999) and an X-ray ultra-fast outflow (UFO) associated to highly-ionized iron (Hasinger et al 2002;Chartas et al 2002;Saez et al 2009;Hagino et al 2017). Furthermore, its high-ionization emission lines, from Lyα to C III] λ1910, are characterized by a significant The reduced spectrum is only available at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/617/A118 blueshift of ∼2500 km s −1 with respect to molecular (Downes et al 1999) and Balmer lines (Oyabu et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…APM 08279 exhibits AGN-driven outflows acting at different scales and involving different gas phases (Chartas et al 2009, Saez & Chartas 2011, Saturni et al 2016, Hagino et al 2017.…”
Section: Discussionmentioning
confidence: 99%
“…For v UFO = 0.22c, and a black hole mass in the range M(BH) = 2 × 10 9 − 10 10 M (Hagino et al 2017 and references therein), we estimated a nuclear outflow rate of 7.7-38 M /yr. The main parameters of the UFO are reported in Table 4.…”
Section: Molecular Outflowmentioning
confidence: 99%
“…On the other hand, it has been suggested that radiative acceleration of UFOs via UV linedriving is possible if they were in a sufficiently low ionization state near their launch points (e.g., Hagino et al 2015Hagino et al , 2017Nomura et al 2016;Nomura & Ohsuga 2017). In this scenario, as the UFOs flow outwards, they become increasingly ionized, until only H-and He-like Fe lines can be detected.…”
Section: Introductionmentioning
confidence: 99%